Low-Cost Production of Chitosan Biopolymer from Seafood Waste: Extraction and Physiochemical Characterization - Karim, Md Mobarok; Lasker, Tahera; Sahin, Md Ali Zaber; Hossain, Md Shajjad; Saputra, Heru Agung (Journal of Research Updates in Polymer Science, 2024)
Chitosan is an abundant natural biopolymer widely used in industrial and pharmaceutical applications. It stands out for its remarkable biodegradability, biocompatibility, and versatility. Herein, we tried to extract chitosan from mud crab (Scylla spp.), a seafood waste abundantly found in Bangladesh’s growing crab farming industry, via a simple low-cost production route. At first, chitin was extracted from crab shells through demineralization and deproteinization to eliminate minerals and proteins. The chitosan biopolymer was then obtained by deacetylation of purified chitin. To evaluate its physicochemical properties, the as-prepared chitosan was characterized by different analyses, such as water and fat binding capacity, solubility, viscosity, molecular weight, fourier transform-infrared, thermogravimetric, scanning electron microscopy, and ash content analysis. The results showed that the crab shell contains around 26.8% chitosan by dry weight, making it an excellent raw material for the massive production of the natural biopolymer chitosan. The prepared chitosan showed fat and water binding capacities of 200-300% and ~680.9%, respectively. Furthermore, it was highly soluble in 1% acetic acid and had an ash content of about 33.7%. Convincingly, the produced chitosan showed great physiochemical properties making it suitable for biomass efficiency, sustainable development, revenue generation, and biomedical applications. In addition, the recycling of seafood waste into a valued product is beneficial to help keep the environment clean, which is among the sustainability goals in Bangladesh and globally.